Metodologia de excitação para identificação de parâmetros dinâmicos de selos anulares - Diaz, Diego Alejandro Godoy (2019)
The choice of the excitation signal is an important step in any identification procedure of rotating machinery. There are applications where the total experiment time, as well as the shaft displacement are boundary conditions which have to be taken into account before performing the test. Thus, the excitation signal used in the actuator must be such that there is an adequate distribution of the energy applied into the system, complying the aforementioned restrictions. In this thesis, a comparisson between the dynamic parameters of annular seals and bearings obtained using several excitation signals is made. Modified multisine signals produced by means of iterative algorithms, which reduce their crest factor and therefore improve the input Signal-to-noise ratio, are also included in this work. Two small-scale test rigs with electromagnetic actuators, developed in the Acoustics and Vibration Laboratory of the Federal University of Rio de Janeiro, were used to perform the experimental tests. It can be observed from the obtained results a noteworthy reduction of the variances when modified multisine signals are used, if compared with the traditional swept or white noise signals